Pavement condition performance on crumb rubber road in Kuala Krai, Kelantan - Zukirnaini, Nazirul Mubin (2020)
Paved roads are the main public transportation infrastructure in Malaysia. Asphaltic pavements require a hefty amount of thoughts and engineering to be made viable to keep up with the growing traffic as the country develops. The constant increase in traffic loads by calls for improvements need to be done in order to maintain a quality, yet economical paved roads. One of the critical breakthroughs is the use of crumb rubber as additive in the binding substance of asphaltic pavements. Thus, this study aims to assess the effectiveness of crumb rubber modified asphalt (CRMA) pavements in Kuala Krai, Kelantan. This research was done through both controlled experiment in a laboratory and also on site. The physical properties of the bitumen in terms of their penetration, softening points, penetration index and flash points have been further tested. For the asphalt mixture, they were tested in regards to their Marshall properties such as stability, Void-In-Mix (VIM), flow and stiffness. The field test begins with the coring test in order to assess the thickness of the asphalt pavement layers in 16 spots along the study location. The densities and bitumen content of the samples were then evaluated. Generally, CRMA proves its efficacy in providing an effectual performance. In almost all aspect of experimentation revealed that CMRA was the better choice. It is relatively stable, with sufficient VIM percentage to provide flexibility. The field test did not contradict with these findings. Conclusively, CMRA is able to accommodate and provide good riding quality while also being durable to sustain all its challenges.